Growth Performance and Haematological Indices of Broiler Chickens Fed on Rice Husk Supplemented with Oyster Mushroom (Pleurotus ostreatus) and Brozyme Enzyme - Dairo , F.A.S.; Ogunlade, S.W. (International Journal of Poultry Science, 2022)
Objective: The present study aimed to investigate the effects of native rice husk on the growth performance and haematology of Broiler Chickens. Materials and Methods: A total of 210 day old broiler chicks of Arbor Acre breeds were fed starter and finisher diets containing (I) Pleurotus ostreatus fungus fermented rice husk (PFFRH) and (ii) exogenous brozyme enzyme supplemented rice husk (ESRH). Different levels of the test feeds (10, 20 and 30%) were included in the broiler diets to replace maize at the two phases. The birds were distributed in a completely randomized design to make a 2×3 factorial arrangement that gave 7 treatments and 3 replicates with 10 birds in each replicate. Results: The results showed that birds fed on the control diet and 10% PFFRH inclusion in the diet, had the highest (p<0.05) average daily weight gain (ADWG), the best feed conversion ratio (FCR) and protein efficiency ratio (PER) for the starter and finisher phases and for the entire 56 days. However, all the parameters were at the lowest level (p<0.05) in the birds fed diet supplemented with 30% ESRH. The treatment interaction effects were the highest (p<0.05) in birds fed the control diet at the starter phase while the treatment groups (PFFRH and ESRH) had similar values for growth parameters at the finisher phase and for the entire experimental period. The haematology and serum chemistry indices included packed cell volume (PCV), red blood cell (RBC), white blood cell (WBC), haemoglobin concentration (Hbc), total protein, albumin, globulin, creatinine, cholesterol, aspartate amino transaminase, alanine transaminase and alkaline phosphatase were within the acceptable range for all the treatment groups. Conclusion: Diets supplemented with 10% PFFRH and 10% ESRH could be optimally used in poultry feed without negative effects on the growth and health status of the broiler birds.